Integrative approaches in Alzheimer’s disease: evaluating the potential of traditional, complementary, and integrative medicine (TCIM) - Sneha Sri, R.; Pavithra, T.; Vinciya, T.; Santhosh Kumar, V.; Harikrishnan, N.; Begum, Rukaiah Fatma; Ankul Singh, S. (Frontiers in Pharmacology, 2025)
This review explores the potential of Traditional, Complementary, and Integrative Medicine (TCIM) as an adjunct to conventional therapies for Alzheimer’s Disease (AD). Unlike pharmaceutical treatments that primarily offer symptomatic relief, TCIM encompasses holistic approaches that target multiple pathophysiological pathways involved in AD, including tau pathology, oxidative stress, mitochondrial dysfunction, and neuroinflammation. Herbal therapies such as Withania somnifera, Ginkgo biloba, and Curcuma longa have shown promising neuroprotective effects in preclinical and limited clinical studies. Mind-body practices like Kirtan Kriya meditation have also demonstrated stress-reduction benefits, addressing modifiable risk factors for AD. While current evidence highlights the potential of TCIM interventions to complement standard care, rigorous validation through high-quality randomized controlled trials remains essential. This review underscores the need for integrative, personalized approaches that synergize traditional and modern medical systems to enhance therapeutic outcomes in AD.